Improving nutrition literacy skills of prospective chemistry teachers: implementing guided inquiry in food additives learning - Imelda Helsy; Muti Sabila Fadila; Riri Aisyah; Ida Farida (EDUSAINS, 2025)
The importance of integrating nutrional literacy into the competenceies of prospective chemistry teachers, which is directed at having knowledge about food, such as understanding various types of food that contain additives and forming healthy lifestyle habits. This study aims to investigate the implementation of guided inquiry in teaching about food additives and to examine its impact on prospective chemistry teachers’ nutrition literacy, thereby contributing to the design of effective educational interventions that connect academic knowledge with everyday health practices. A mixed-methods sequential explanatory approach was employed with the instruments of questionnaires, interviews, and N-Gain analysis of pretest-posttest to assess improvements in the nutrition literacy of prospective chemistry teachers. The sample of this research involved 30 sixth-semester students from the Chemistry Education Program at a university in Bandung. The results showed that prospective chemistry teachers demonstrated adequate knowledge of food composition and additives, the ability to manage a balanced diet, and positive attitudes toward healthy food consumption. The N-Gain analysis revealed a significant improvement, with an overall average of 0.72 (high category). Specifically, the high-achievement group achieved 0.78 (high), the low-achievement group 0.61 (high), and the moderate-achievement group 0.78 (moderate). Interview findings reinforced these results, revealing that prospective chemistry teachers  were able to identify food types and nutritional values, distinguish between natural and synthetic additives, recognize the importance of safe consumption limits, and highlight challenges related to reporting hazardous additives and accessing foods with fewer additives. In conclusion, guided inquiry learning enhances academic ability with fostering active learning, deeper understanding, and higher-order thinking, so the results show increase prospective chemistry teachers’ nutrition literacy and equipping them with practical decision-making skills, making it a valuable educational intervention for fostering healthier lifestyles.